IMPLEMENTASI E-PROCUREMENT DALAM PENGADAAN BARANG DAN JASA DI BAGIAN LAYANAN PENGADAAN BARANG DAN JASA PEMERINTAH (BLPBJ) SEKRETARIAT DAERAH KOTA MAKASSAR - Ahmad Ahmad; Abd. Kadir Adys; Nasrul Haq (JPPM: Journal of Public Policy and Management, 2020)
This study aims to determine the implementation of E-Procurement in the procurement of goods and services in the Procurement Services Section of the City of Makassar Regional Secretariat. The type of research used is qualitative research. Data analysis techniques using steps of data collection, data reduction, data presentation, verification of data that are qualitative in nature, to draw conclusions. The results showed that there were five indicators: (1) BLPBJ Makassar City human resources suppressed the readiness of character qualities that are continuing; (2) Online communication provides accessibility and flexibility; (3) The objective of going hand in hand is between Tender and Non-Tender for the Makassar City DPRD game; (4) The environment supports the Makassar City LPSE in terms of politics and economics and not the general public; (5) Compliance of the implementor on the condition of direct appointment to the deposited contractor requires that the compliance of the implementor in handling Direct Procurement (PL) has not been maximized.